Educators’ Perceptions of Challenges to Transformative Learning in Palestinian Kindergartens: A Study of Demographic Differences in the Salfit Governorate - Nafiz Ali Ahmad (Universitas Negeri Semarang, 2025)
This study investigates the challenges and obstacles to implementing transformative learning in early childhood education institutions in Palestine, using the Salfit Governorate as a case study. Transformative learning, which emphasizes critical reflection, learner empowerment, and personal growth, remains underutilized in Palestinian kindergartens due to various systemic, cultural, and institutional barriers. A quantitative cross-sectional survey methodology was adopted, and data were collected through a structured questionnaire distributed to 262 principals and teachers working across 56 kindergartens in the region. The results indicated a high level of perceived challenges across five key domains: curriculum rigidity, insufficient professional development, lack of resources, societal resistance, and weak institutional support. Significant differences in perceptions were found based on job title, academic qualification, yesrs of experience, type of kindergarten, and geographic location, while academic qualification showed no significant effect. The study highlights systemic challenges, with institutional support gaps (reported by principals) and rural cultural resistance emerging as critical barriers. These findings suggest that transformative learning in Palestine may require context-sensitive strategies, though further research is needed to evaluate specific reforms.